2006
DOI: 10.4049/jimmunol.177.3.1481
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Domain of Fas Ligand Costimulates TCR Signals

Abstract: Productive T cell activation generally requires costimulation in addition to a signal delivered through the TCR. Although FasL is well-characterized for its capacity to deliver a death signal through Fas, this TNF family member can also transmit a reverse signal to enhance Ag-driven T cell proliferation. In this study, we define this reverse signal through FasL as costimulation by showing it requires TCR coengagement and is CD28 independent. We demonstrate that FasL-mediated costimulation drives FasL recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 71 publications
2
64
0
Order By: Relevance
“…To define more precisely the role of ADAMs in FasL shedding, we used a panel of established MEF cell lines that were generated from mouse embryos with a targeted deletion of different ADAM proteases as 40 kDa FasL is cleaved in the extracellular domain by a protease activity, generating a soluble ectodomain (sFasL) and a membrane-bound 18 kDa NTF termed NTF1, which can be further processed. The antibody G247-4 reacts with an extracellular epitope, whereas Ab3 detects intracellular determinants.…”
Section: Resultsmentioning
confidence: 99%
“…To define more precisely the role of ADAMs in FasL shedding, we used a panel of established MEF cell lines that were generated from mouse embryos with a targeted deletion of different ADAM proteases as 40 kDa FasL is cleaved in the extracellular domain by a protease activity, generating a soluble ectodomain (sFasL) and a membrane-bound 18 kDa NTF termed NTF1, which can be further processed. The antibody G247-4 reacts with an extracellular epitope, whereas Ab3 detects intracellular determinants.…”
Section: Resultsmentioning
confidence: 99%
“…33 Much less is known about the molecular mechanisms underlying its capacity to transduce nonapoptotic signals into the ligand-bearing cell. FasL reverse signaling has been shown to enhance T-cell proliferation, [11][12][13] and a recent publication has demonstrated that expression of the cytoplasmic FasL domain alone is sufficient to costimulate T-cell receptor signals. 11 Nevertheless, it remains unclear exactly how the FasL ICD is engaged in the transmission of such costimulatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…FasL reverse signaling has been shown to enhance T-cell proliferation, [11][12][13] and a recent publication has demonstrated that expression of the cytoplasmic FasL domain alone is sufficient to costimulate T-cell receptor signals. 11 Nevertheless, it remains unclear exactly how the FasL ICD is engaged in the transmission of such costimulatory signals. Our data reveal a novel regulated processing of endogenous FasL in T-cells by the metalloproteinase ADAM 10 and the intramembrane protease SPPL2a, which ultimately leads to liberation of the FasL ICD into the cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations